Preservation of arts and culture through edutourism village of Mentaraman in Malang East Java - Desti Nur Aini; Agung Winarno; Wiwik Wahyuni; Sri Prameswari Indriwardani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
There are many kinds of community efforts in preserving their local culture, one of which is to carry out routine activities that are integrated with the village celebration agenda so that they become a medium for demonstrating the performance of their local cultural arts potential. This Community Service (PkM) activity aims to package cultural preservation efforts through the formation of an educational tourism village (eduwisata). The location is in the village of Mentaraman, Pagelaran Village, Malang Regency, East Java. The stages used were identification of potential and problems, Focus Group Discussions (FGDs), program preparation, socialisation, and trial visits. Analysis of the results used the 6P simultaneous stage. The results of the community service programme are in the form of a tourism package document supported by an increase in skills and a variety of performing arts as well as the involvement of local communities in management. Recommendations include the need to increase the capacity of local tour guides, the participation of artists, and the use of information technology to support digital-based promotions.